2014
DOI: 10.1074/jbc.m114.547919
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Marrow Adipogenesis Is Linked to Increased Expression of RANKL

Abstract: Background:The osteoclastogenic cytokine RANKL is expressed in various cell types, including osteoblasts, osteocytes, and lymphocytes. Results: RANKL expression is induced during adipogenesis through the action of C/EBP␤ and/or C/EBP␦, and RANKL-positive preadipocytes increase in aging marrow along with down-regulation of osteoprotegerin. Conclusion: Adipogenesis is linked to osteoclastogenesis through RANKL expression. Significance: Increased marrow preadipocytes with aging may contribute to osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(85 citation statements)
references
References 42 publications
5
77
2
1
Order By: Relevance
“…It is of note that Sinha et al also reported that Gsα OsxKO bones showed an 8-fold increase in Pref-1 expression, a marker of pre-adipocytes, compared to controls (Sinha et al, 2014). And previously, Takeshita et al noted that in aging mouse marrow, with significant adiposity, the proportion of RANKL + /Pref1 + cells was markedly increased (Takeshita et al, 2014). In addition, we noted that BMSCs derived from the mutants when grown in osteogenic, adipogenic or no differentiation media, expressed consistently higher levels of Rankl and greater Rankl/Opg ratios than controls (Figure S6A).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is of note that Sinha et al also reported that Gsα OsxKO bones showed an 8-fold increase in Pref-1 expression, a marker of pre-adipocytes, compared to controls (Sinha et al, 2014). And previously, Takeshita et al noted that in aging mouse marrow, with significant adiposity, the proportion of RANKL + /Pref1 + cells was markedly increased (Takeshita et al, 2014). In addition, we noted that BMSCs derived from the mutants when grown in osteogenic, adipogenic or no differentiation media, expressed consistently higher levels of Rankl and greater Rankl/Opg ratios than controls (Figure S6A).…”
Section: Discussionmentioning
confidence: 94%
“…To further characterize RANKL positive cells in the bone marrow we performed extensive flow cytometry using the RANKL antibody in combination with Pref-1 as the marker of pre-adipocytes (Takeshita et al, 2014) and B220 as a B cell lineage marker (Figure 6) (Smas and Sul, 1993). FACS analysis revealed that in B220 negative cells, the percentage of Pref-1 positive cells was increased in Prx1Cre;PTH1R fl/fl , Tm fl/+ mice compared to control heterozygous littermates (Figure 6A left, Q1+Q2).…”
Section: Resultsmentioning
confidence: 99%
“…These cells also show enlargement, telomere shortening, or p53/p21-mediated DNA damage accumulation, impaired DNA methylation or histone acetylation, and increased levels of ROS and nitric oxide (NO) (6569). Although age-dependent mechanisms underlying adipogenesis-favoring MSC differentiation are not as yet fully understood, possible molecular changes have been reported, including activations of peroxisome proliferator-activated receptor gamma 2 and CCAAT/enhancer binding protein (70, 71). Adipogenesis enhancement in aged BM (72) might be linked to dysregulation of insulin growth factor signaling (27), changes in extracellular matrix composition, and decreased bone formation (73, 74).…”
Section: Hematopoietic Agingmentioning
confidence: 99%
“…Paraffin-embedded BM biopsy specimens were stained with H&E and for Pref-1, a welldescribed marker for preadipocytes. 18,20 Balloon-like mature adipocytes and Pref-1epositive preadipocytes were enumerated. The results revealed significantly greater Pref1epositive cells in the BM of patients with MM compared with healthy BM, indicating an increase in the preadipocyte population in MM patients ( Figure 1, A and B).…”
Section: Patients With MM Have Enhanced Bone Marrow Adipogenesismentioning
confidence: 99%